Produção e caracterizações de superfícies antimicrobianas e bioativas sobre titânio - Zaniolo, Karina Marchi (2019)
Titanium (Ti), being biocompatible and presenting chemical stability and good mechanical properties, is the most used material for manufacturing dental implants. However, implants present a high number of failures mainly due to bacterial infections and aseptic loosening. Infections can be prevented by the addition of antimicrobial agents to the surface of these implants and the formation of a bioactive surface accelerates the osseointegration process preventing loosening. In this context, the aim of this work was to modify the Ti surface so as to promote an early osseointegration and to provide antimicrobial activity. Thus, porous and bioactive surfaces of titanium oxide were produced on titanium by the insertion of calcium and phosphorus ions by the micro-arc oxidation technique. Afterwards, silver was deposited (via electroplating or by dripping a colloidal silver nanoparticle solution - NpAg) on this surface (Ti/TiO2) to provide antimicrobial activity. In addition, to minimize the cellular toxicity of silver, these surfaces were coated with the poly(lactic acid) polymer (PLA). The NpAg were synthesized by a reproducible method and characterized by UV-Vis, MET, DLS spectroscopy and zeta-potential measurements. On the other hand, the surfaces of Ti (polished, anodized, anodized/Ag and anodized/Ag/PLA) were characterized by SEM, EDS and XRD. These surfaces exhibited antimicrobial activity against S. aureus, good biocompatibility with pre-osteoblasts in cell-viability tests, extracellular matrix mineralization, and cell adhesion and proliferation. Furthermore, the PLA coating was effective for the controlled release of Ag in PBS medium. The various surfaces produced in this work are promising for use as implants and may be especially useful in patients who have periodontal disease, or who have poor bone stock that requires greater stimulation for osteogenesis.